Recognition of facial expressions and personal features as a tool to identify people in a public transport system - Rojas Villanueva, Uwe (2022)
The use of artificial intelligence nowadays has many applications. This paper proposes the use of artificial intelligence based facial recognition using machine learning to identify through Python language, people who are missing, abducted or have committed crimes. The Jetson Nano development platform identifies and sends an alert via SMS text message to the monitoring and information control units for decision making and response. This device is based on the Ubuntu operating system, which can work standalone, is small, and allows easy accessibility in confined spaces. The tool can also predict people’s moods through gestures made on the face with the application of the Viola-Jones algorithm.